Dukungan Keluarga Sebagai Faktor Penentu Prestasi Akademik Anak Disabilitas Netra - M.Krisna Bagus Virgiana; Intan Nurul Azizah; Salwa Tadzkirotul Aula; Irma Masfia; Zulfa Fahmy (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The aim of this research is to assess the importance of family support in encouraging academic success in children with visual disabilities. The main study in this research focuses on the role of the family in encouraging the academic achievement of children with visual disabilities and the approaches taken. Data collection in this research was through in-depth interviews. The results of this study highlight the important role of family support, particularly parental involvement, in promoting good outcomes for students with visual disabilities. Apart from support from family, educators and peers also play an important role in strengthening self-confidence, academic performance and improving skills in children with visual disabilities. Increased parental support is associated with increased motivation and empowerment to realize the potential of children with visual disabilities.